2021
DOI: 10.1007/s40726-021-00174-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Reduction of Cr(VI): Operational Challenges and Feasibility

Abstract: Purpose of Review Hexavalent chromium, Cr(VI), and trivalent chromium, Cr(III), are two chromium compounds with practical importance due to their high occurrence and solubility in the environment. Current Cr(VI) treatment techniques involve chemical reduction of Cr(VI) to Cr(III), which posed serious threat to workers and environment notably from long exposure and toxic fumes.Recent Findings Numerous reports have demonstrated the feasibility of using biological processes for the treatment of Cr(VI) industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 93 publications
(100 reference statements)
0
9
0
Order By: Relevance
“… 16 Mass transport effects induced by the outer membrane of Gram-negative bacteria and the thin cell wall of peptidoglycan containing reductase promote the biosorption of heavy metals by Gram-negative bacteria. 15 , 16 We used the microfluidic method for the encapsulation of E. coli and Bacillus subtilis , treating aqueous solutions of 5, 25, and 50 mg/L hexavalent chromium. We found that 5 mg/L of hexavalent chromium was absorbed at a higher rate than the others.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 16 Mass transport effects induced by the outer membrane of Gram-negative bacteria and the thin cell wall of peptidoglycan containing reductase promote the biosorption of heavy metals by Gram-negative bacteria. 15 , 16 We used the microfluidic method for the encapsulation of E. coli and Bacillus subtilis , treating aqueous solutions of 5, 25, and 50 mg/L hexavalent chromium. We found that 5 mg/L of hexavalent chromium was absorbed at a higher rate than the others.…”
Section: Resultsmentioning
confidence: 99%
“… 16 A variety of microorganisms have been shown to be able to reduce Cr(VI) directly or indirectly, and their metabolites are also capable of acting as reducing agents, such as organic acids, amino acids, sulfides, and divalent iron. 2 , 15 , 16 Intracellular and membrane-bound Cr(VI) reduction is usually mediated by flavin-dependent reductase and hydrogenase, respectively, while extracellular and periplasmic Cr(VI) reduction is accomplished by cytochromes. 2 Intracellular reduction of Cr(VI) is the common pathway, and the influencing factors are NADH, flavin proteins, and other heme proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations